Enhancement of the Efficiency of Bioethanol Production by Saccharomyces cerevisiae via Gradually Batch-Wise and Fed-Batch Increasing the Glucose Concentration - Chang, Yi-Huang; Chang, Ku-Shang; Chen, Chien-Yu; Hsu, Chuan-Liang; Chang, Tsan-Chang; Jang, Hung-Der (Fermentation (Basel), 2018)
High initial glucose concentrations may inhibit glucose utilization and decrease ethanol fermentation efficiency. To minimize substrate inhibition, the effects of feeding yeast with different glucose concentrations on the ethanol production by batch and fed-batch cultures in a 5-L fermentor were investigated. When a batch culture system with Saccharomyces cerevisiae was used for ethanol fermentation with glucose concentrations ranging 10–260 g/L, as a result, 0.2–7.0 g/L biomass and 5.1–115.0 g/L ethanol were obtained. However, substrate inhibition was observed with the initial glucose concentrations greater than 200 g/L in the fermentative media. When a fed-batch culture system (an initial glucose concentration of 180 g/L and total glucose concentration of 260 g/L) was performed, the maximum ethanol concentrations and ethanol yield were significantly higher than those of the batch cultures. The cell biomass, maximum ethanol concentration, and ethanol yields for the fed-batch fermentation cultures were 8.3 g/L, 130.1 g/L and 51% (100% of the theoretical value), respectively. The results indicated that high ethanol concentration and ethanol yield could be achieved by the fed-batch cultures with total glucose concentrations up to 260 g/L.